Dolichopus nimbatus Parent, 1927 revisited, with two new synonyms (Diptera: Dolichopodidae) - Pollet, Marc (Zootaxa, 2017)
On the basis of comparison between the female holotype of Dolichopus nimbatus Parent and the female paratype of D. balius Meuffels, and comparison of a male paratype of D. balius with the description of D. thalhammeri Knézy, D. balius and D. thalhammeri are designated junior synonyms of D. nimbatus. Dolichopus nimbatus ranges from northern France and Belgium to southern Turkey. Ecological features might explain its rarity in collections.